When treating medial patellar luxation in dogs is a block trochleoplasty superior over a wedge trochleoplasty? - Norell Candetoft, Maria (Veterinary Evidence, 2022)
PICO question As part of the surgical correction for medial patellar luxation in dogs, which procedure results in a better outcome for the patient: block or wedge recession trochleoplasty? Clinical bottom line Category of research question Treatment The number and type of study designs reviewed Three studies satisfied the inclusion criteria for answering the PICO; one cadaver study, one retrospective observational study and one clinical case series Strength of evidence Weak Outcomes reported Postoperative complications including reluxation rates. Ex vivo: Trochlear groove depth, patella articular contact, percentage of recessed trochlear surface area, resistance to medial patella luxation Conclusion There is only weak evidence to support block recession trochleoplasty over wedge recession trochleoplasty as part of the surgical correction for medial patella luxation in dogs. Both procedures are associated with a good clinical outcome. There are some proposed benefits to trochlear block recession made from an ex vivo study comparing the two procedures. These include an increased patellar volume under the trochlear ridges when the stifle is extended. The articular contact and recessed trochlear surface area were also increased in the trochlear block recession group when compared to trochlear wedge recession. However, the clinical relevance of these perceived benefits remains unproven. In practice, and until prospective randomised controlled trials are carried out, veterinary surgeon preference and previous experience remain relevant factors in choosing which procedure to perform How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.